Blogging for dummies - Gardner, Susannah; Birley, Shane (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2010)
A plain-English guide to blogging. Learn how to set up, publish, and maintain a blog that draws readers.
Getting started with blogs -- Setting up your blog -- Fitting in and feeling good -- Going beyond words -- Marketing and promoting your blog -- Getting business-y with it -- The part of tens.
Print version record.
English.
John Wiley and Sons
Keywords: Blogs; Blogues; blogs; COMPUTERS -- Web -- Blogs; Blogs